2015
DOI: 10.1002/ejlt.201500200
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of five bacterial WS/DGAT acyltransferases regarding the synthesis of biotechnologically relevant short‐chain‐length esters

Abstract: For the biotechnical production of biofuels, oleo‐, or fine chemicals bacterial wax ester synthase/acyl‐Coenzyme A:diacylglycerol acyltransferases (WS/DGAT) are discussed as interesting candidates for in vivo esterification reactions. In this study, the suitability of selected acyltransferases for the conversion of non‐physiological substrates like short‐chain‐length alcohols and short‐chain length or even branched acyl‐CoAs has been investigated. In vitro analyzes of purified AtfA and AtfA(G355I) from Acineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…To identify new WSD enzymes in the bacterium M. aquaeolei VT8, a BLAST homology search on the genome of M. aquaeolei VT8 using the amino acid sequence of AbWSD1 was performed. In addition to the four already known and partly characterized WSD MaWSD1, MaWSD2, MaWSD3, and MaWSD4 (Barney et al, 2012(Barney et al, , 2013(Barney et al, , 2015Petronikolou and Nair, 2018;Röttig et al, 2016;Villa et al, 2014), a putative fifth WSD (MaWSD5, Maqu_3411) was identified. While characterizing MaWSD5, the existence of the protein was also mentioned in a book chapter (Knutson et al, 2017).…”
Section: Aquaeolei Vt8 Possesses a Fifth Wsdmentioning
confidence: 95%
“…To identify new WSD enzymes in the bacterium M. aquaeolei VT8, a BLAST homology search on the genome of M. aquaeolei VT8 using the amino acid sequence of AbWSD1 was performed. In addition to the four already known and partly characterized WSD MaWSD1, MaWSD2, MaWSD3, and MaWSD4 (Barney et al, 2012(Barney et al, , 2013(Barney et al, , 2015Petronikolou and Nair, 2018;Röttig et al, 2016;Villa et al, 2014), a putative fifth WSD (MaWSD5, Maqu_3411) was identified. While characterizing MaWSD5, the existence of the protein was also mentioned in a book chapter (Knutson et al, 2017).…”
Section: Aquaeolei Vt8 Possesses a Fifth Wsdmentioning
confidence: 95%
“…Atf1 and AtfA can accept a wide range of alcohols, whereas Eeb1 seems restricted to shortchain alcohols (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…The specific enzyme activity of purified acyltransferase was measured indirectly using 5,5=-dithiobis-(2-nitrobenzoic acid) (DTNB) at 37°C (38). The cuvette was filled with 720 l prewarmed buffer (50 mM sodium phosphate, pH 7.4), 100 l of a 2 mM DTNB solution in buffer, 120 l dimethyl sulfoxide (DMSO), 20 l of the acyl-CoA stock solution (1 mM in DMSO), and 20 l of a linear alcohol (4 mM in DMSO) or 1,2-dipalmitoyl-sn-glycerol (DPG; 5 mM in DMSO).…”
Section: Methodsmentioning
confidence: 99%